Competition lifespan survival analysis in the Norwegian‐Swedish Coldblooded Trotter racehorse. (2nd August 2018) - Velie, B. D.; Jäderkvist Fegraeus, K.; Ihler, C. F.; Lindgren, G.; Strand, E.
Summary: Background: Studies of large racing populations have established clear differences in the career profile of stallions, mares and geldings. Multiple studies have also demonstrated positive effects on racing careers for horses that commence racing at a younger age. However, the applicability of these studies to small, native racing populations is unknown and warrants investigation. Objectives: To provide summary statistics for performance outcomes for the Norwegian‐Swedish Coldblooded Trotter and to document and provide evidence on the current differences in racing careers across age at first start groups, sexes and country of birth. Study design: Cohort study. Methods: Performance data on the population of Norwegian‐Swedish Coldblooded Trotters born between 2000 and 2009 (n = 14, 548) were acquired and used to describe and compare the racing careers of this native racing breed. Career length, career starts and career earnings were evaluated. Kaplan–Meier survival curves, stratified by sex, age group and country of birth were produced for career length. A Cox proportional hazards model was fitted to assess factors influencing the hazard rate of retirement from racing. Results: Log‐rank test for equality of career length survival functions showed significant differences (P<0.001) across sexes, countries of birth and age at first start groups. An increased age at first start increased the hazard rate of retirement from racing. Main limitations: Racing career length is influenced by many factors. While this study accounts for some of the known influences on career length, the analysis would be strengthened by the inclusion of additional information, such as trainer and reasons for retirement. Conclusions: The results of this study suggest no adverse effects to the racing of young Norwegian‐Swedish Coldblooded trotters. The study also establishes significant differences in career length based on sex and identifies that these differences are the opposite of what is seen in many other horse racing breeds. The Summary is available in Spanish – see Supporting Information